On agro-industrial assessment of territorial lands of Tartar region (on the example of Borsunlu village) - Omarov, Sahib (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Annotation: Due to the climatic features of Azerbaijan, its soil is subject to severe erosion. Thus, eroded (washed, loosened, loosened, etc.) soils are often found in the country. This is explained by the fact that, as is clear from the morphological description of the section in the study area, the color of the soil here is brown in the upper layer, light brown in the middle layer, and straw in the last layer. The structure is heavy clayey in the upper layer, medium clayey in the middle layer and in the last layer. Roots and rhizomes, insect tracts, rust spots are found in new derivatives and fruits. These soils are boiled under the influence of 10% hydrochloric acid (HCl). Hygroscopic moisture is less moisture throughout the profile. The transitions in the genetic layers are clear and gradual.It should be noted that in general, erosion processes lead to erosion and destruction of the topsoil. According to the results of laboratory analysis of soil samples on different soil types from different experimental areas, the actual soil fertility determined for the suitability of different types of agricultural crops, a number of types of agricultural culture. grapes and clover-cheese.This article presents the results of a comparative analysis of the degree of erosion of the land cover formed in the territory of the Tartar region of the Republic of Azerbaijan using aerospace images and studied. Key words: Soil-forming rocks, soil granulometric composition, physicochemical properties, soil mineralogical composition, soil profile, genetic layers, parent rock, erosion process.